STUDY AND OPTIMIZATION OF EFFICIENCY AND DURABILITY COMBINED TOOL CORE DRILL-TAP - L. M. Aliomarov; N. M. Vagabov; A. Z. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The integrated studies identified factors influencing wear resistance of tapping and part of the combined tool, which has been studied and optimized its kinetics. The influence of tool wear on geometrical figures thead, performance, torque. The main factors influencing the performance of processing threads. As a result of the study, it was found that the main factors are the cutting speed (V) limit the temporary v resistance of the material to be processed and the reverse cone angle δ. In order to optimize these parameters a full-factorial experiment. On the basis of the received data was built a graphical model of the optimum, which allows you to define basic settings for processing (V, φ), depending on the ultimate strength of the material and shows the kind of stability and performance of the tool.